„Bildung – wychowaniem do autentyczności?” Neohumanistyczne vs. romantyczne rozumienie koncepcji samokształcenia - Kopeć, Anna (Filozofia Publiczna i Edukacja Demokratyczna, 2017)
The article claims that the modern problem with subjectivity, lack of the self, has got its roots in Romanticism and a mistake made then. At the turn of 18th and 19th century authenticity was mistakenly identified with self-creation. This identification is connected with a change of understanding the conception of self-formation, Bildung. In order to show the change, the article presents neohumanistic understanding of Bildung (focused on J. W. Goethe and W. Humboldt) and romantic one (focused of F. Schlegel). By confronting these two approaches, the article presents the thesis that Bildung which leads to being a self, having an identity, cannot postulate independency from the world. However, although a man is responsible for the shape of his character, the content needed for the self-formation lies beyond himself.